Concomitant intramyocardial and hepatic hydatid cysts diagnosed by multi-modality imaging: A rare case report - Nguyen, Hoai Thi Thu; Pham, Viet Tuan; Duong, Hung Duc; Kirkpatrick, James N.; Taylor, Walter Robert; Pham, Hung Manh (Frontiers in Cardiovascular Medicine, 2022)
Cardiac echinococcosis is a potentially fatal form of hydatid disease, yet, its diagnosis and treatment of cardiac echinococcosis are challenging due to the variability of clinical manifestation and to its various, unpredictable preoperative complications. Multi-modality imaging provides important guidance for the treatment and decision- making. We report a rare case of a 50-year-old female who had concomitant cardiac and hepatic hydatid cysts. She presented with abdominal pain and elevated eosinophilic white blood cell. The initial abdominal ultrasound and computerized tomography revealed a large cyst in the liver. An intra-myocardial cyst was detected upon two-dimensional echocardiography. Three-dimensional echocardiography increased the confidence level of two-dimensional echocardiography by displaying the three-dimensional volume of the cyst and allowing visualization of its spatial characteristics and the relationships with adjacent cardiac structures, which was subsequently confirmed at surgery. Multi-detector computed tomography and magnetic resonance imaging helped localize and define the typical morphologic features of the cyst. Serology and antigen detection were used for diagnosis. This rare case underlines the integration of clinical, multimodality imaging and pathological data in the diagnosis of concomitant intramyocardial and hepatic hydatid cysts. Surgical resection of the cysts and anthelminthic medication were successful in the management of this patient. Keywords: hydatid cyst, cardiac echinococcosis, intramyocardial hydatid cyst, three-dimensional echocardiography, multi-modality imaging.